2006
DOI: 10.1002/jcb.20760
|View full text |Cite
|
Sign up to set email alerts
|

The significance of telomeric aggregates in the interphase nuclei of tumor cells

Abstract: Telomeres are TTAGGG repetitive motifs found at the ends of vertebrate chromosomes. In humans, telomeres are protected by shelterin, a complex of six proteins ( . In the present overview, we will discuss the role of telomeres in genome stability, recent findings on three-dimensional (3D) changes of telomeres in tumor interphase nuclei, and outline future avenues of research. J. Cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 50 publications
(75 reference statements)
3
89
0
Order By: Relevance
“…Heterochromatin Protein 1 (HP1) has been shown to form a complex with A-type lamins and LAP-2α, 49 and therefore could participate in the and their relevance for telomere metabolism remain unknown. 42 Interestingly, the 3D organization of telomeres is altered in tumor cells, 38,43 and in senescent cells that present defects in the nuclear lamina. 44 This data suggests a relationship between changes in nuclear distribution of telomeres and alterations of telomere metabolism observed during senescence and immortality.…”
Section: A-type Lamins and Telomere Structure Length And Functionmentioning
confidence: 99%
“…Heterochromatin Protein 1 (HP1) has been shown to form a complex with A-type lamins and LAP-2α, 49 and therefore could participate in the and their relevance for telomere metabolism remain unknown. 42 Interestingly, the 3D organization of telomeres is altered in tumor cells, 38,43 and in senescent cells that present defects in the nuclear lamina. 44 This data suggests a relationship between changes in nuclear distribution of telomeres and alterations of telomere metabolism observed during senescence and immortality.…”
Section: A-type Lamins and Telomere Structure Length And Functionmentioning
confidence: 99%
“…For example, in fibroblasts, the activation of c-Myc lead for an abrupt aggregation of telomeres thus leading to the suggestion that this may contribute to chromosomal fusions followed by repeated cycles of breakage-bridge fusions. 23 Soon after these initial descriptions of CIN, it was demonstrated that c-Myc alters the genome at another level. Vafa et al 1 observed that the deregulation of the oncoprotein was accompanied by the induction of reactive ROS and double-stranded DNA breaks, as evidenced by increased TUNEL positivity and the focal accumulation and colocalization of g-H2AX, hMre11, and BRCA1.…”
Section: The "Oncogene From Hell" Reduxmentioning
confidence: 99%
“…5 Mononuclear H cells are the precursors of multinuclear RS cells, [6][7][8][9] and endomitotic multinucleation is associated with disturbed cytokinesis and jumping translocations 10,11 pointing to a severe telomere dysfunction. 12,13 Telomeres are the nucleoprotein complexes at the ends of chromosomes in which a number of specific proteins, either binding telomere proteins directly or a protein complex, termed 'shelterin,' is directly associated with telomeric DNA. [14][15][16] Profound changes in the three-dimensional (3D) nuclear organization of telomeres are the hallmark of the transition from mononuclear H cells to multinuclear RS cells in EBVnegative Hodgkin cell lines and in classical EBV-negative HL.…”
mentioning
confidence: 99%